Implementation of assessment and evaluation for children with special needs at RA Assakinah - Trisniarti, Susanti; Julyana, Devy; Aprilia Pangesti, Dian; Nurkholisoh, Aliya; Hidayati, Nur; Wulansuci, Ghina (Tunas Siliwangi, 2025)
Evaluation and assessment is an important educational process to monitor, measure, and diagnose children's development. The problem found based on the results of observations is that there is no evaluation and assessment for children with special needs in PAUD institutions. This research aim is to examine the implementation of assessment and evaluation for children with special needs at RA Assakinah. The research method used was qualitative with a qualitative descriptive approach. The research subjects were one head of the Institute and five educators from Raudhatul Athfal Assakinah, Ngamprah District. Collect data techniques by conducting interviews and documentation. The data analysis used is data display and data reduction. The research results show the implementation of evaluation and assessment for children with special needs uses assessment checklist instruments, anecdotes, work results, and photos of activities